2019
DOI: 10.1186/s12882-019-1555-z
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy in a contemporary cohort of autosomal dominant polycystic kidney disease patients

Abstract: BackgroundPatients with Autosomal Dominant Polycystic Kidney Disease (ADPKD) often develop hypertension in childhood or early adulthood. Although this could result in left ventricular hypertrophy (LVH), a major risk factor for cardiovascular morbidity and mortality, prior studies of LVH in ADPKD have yielded conflicting results. We estimated the prevalence of LVH using consensus echocardiography criteria and examined the independent association of ADPKD severity with LV mass in a contemporary cohort of ADPKD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…44 These medications play a major role in the regression of LVH. 45 The early and aggressive management of hypertension with angiotensin-converting enzyme inhibitors and angiotensin receptor blockers is reported to be the main reason why the prevalence of LVH may be lower in ADPKD compared with other patients with CKD. The HALT PKD trial reported only a 4% prevalence of LVH in its large cohort of hypertensive patients with ADPKD.…”
Section: Discussionmentioning
confidence: 99%
“…44 These medications play a major role in the regression of LVH. 45 The early and aggressive management of hypertension with angiotensin-converting enzyme inhibitors and angiotensin receptor blockers is reported to be the main reason why the prevalence of LVH may be lower in ADPKD compared with other patients with CKD. The HALT PKD trial reported only a 4% prevalence of LVH in its large cohort of hypertensive patients with ADPKD.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to intrarenal activation of the renin-angiotensin system by local cystic destruction and a high incidence of hypertension [ 13 , 20 ]. Placebo-controlled trials are not available for patients with ADPKD, but the decrease over time of the very high incidence of left ventricular hypertrophy in this group may be attributable to the more intensive treatment approaches to hypertension [ 86 ]. In the HALT-PKD A study, more intensive lowering of blood pressure (but not single vs. dual RAS blockade) resulted in a greater decline of left ventricular mass index in adults with early ADPKD [ 87 ].…”
Section: Managementmentioning
confidence: 99%
“…According to some studies, increased LVMI in normotensive ADPKD patients correlated with 24h ambulatory systolic BP or with an exaggerated systolic BP response to exercise [ 8 , 59 ]. However, the prevalence of increased LVMI is highly variable in the literature ranging from up to 48% in older series [ 26 ] down to 20% or less in more recent reports [ 60 ]. Noteworthy, the percentage of increased LVMI measured by magnetic resonance imaging (a gold standard method for assessing LV mass) [ 14 ] in the HALT-PKD study [ 61 ] involving 558 hypertensive ADPKD patients under pharmacological therapy showed a prevalence of left ventricular hypertrophy (LVH) as low as 0.93%.…”
Section: Discussionmentioning
confidence: 99%
“…The Chronic Renal Insufficiency Cohort (CRIC) Study [ 65 ] showed an association between the degree of loss of renal function and abnormalities in cardiac structure, mainly higher left ventricular mass, but polycystic kidney disease had been excluded from the trial. Chen et al [ 60 ] observed an inverse correlation between eGFR and LVMI. In the present series, eGFR was not an independent determinant of LVMI by multivariable linear regression.…”
Section: Discussionmentioning
confidence: 99%